Characterization of the Ca2+-Gated and Voltage-Dependent K+-Channel Slo-1 of Nematodes and Its Interaction with Emodepside - Kulke, Daniel; von Samson-Himmelstjerna, Georg; Miltsch, Sandra M.; Wolstenholme, Adrian J.; Jex, Aaron R.; Gasser, Robin B.; Ballesteros, Cristina; Geary, Timothy G.; Keiser, Jennifer; Townson, Simon; Harder, Achim; Krücken, Jürgen (PLOS Neglected Tropical Diseases, 2014)
Author Summary Emodepside is an anthelmintic introduced into the market as an ingredient of different dewormers for cats and dogs, and is the only member of the cyclooctadepsipeptide class which has been commercialized. The voltage-gated and calcium-activated potassium channel Slo-1 has been implicated in the mode of action of emodepside, but evidence for direct emodepside-induced changes on the properties of Slo-1 channels has not been reported. Emodepside is active against a broad spectrum of parasitic nematodes, but the putative target Slo-1 has only been described for the model nematode Caenorhabditis elegans, and for relatively closely related strongylids. Here, Slo-1 channels of ascarids, filariae and trichocephalids are described. Unexpectedly, in the latter group two distinct Slo-1 channels are encoded in their genomes. The C. elegans Slo-1a channel was expressed in Xenopus laevis oocytes. After membrane depolarization without experimentally increasing intracellular Ca2+, no Slo-1 specific currents were observed. In contrast, very large Slo-1-specific currents were observed after preincubation of oocytes with emodepside, suggesting that the drug opens the C. elegans Slo-1a channel irreversibly. This is the first report demonstrating direct interaction of a cyclooctadepsipeptide with a Slo-1 channel, which substantially enhances our understanding of the mode of action of this drug class.